CYP2C19 and nongenetic factors predict poor responsiveness to clopidogrel loading dose after coronary stent implantation. (September 2008) - Geisler, Tobias; Schaeffeler, Elke; Dippon, Juergen; Winter, Stefan; Buse, Verena; Bischofs, Christian; Zuern, Christine; Moerike, Klaus; Gawaz, Meinrad; Schwab, Matthias
Aims: To investigate an association of responsiveness to clopidogrel loading dose with genotypes of cytochrome P450 (CYP) 2C19, other CYP isozymes and nongenetic factors in patients with coronary artery disease.Materials & methods: Genotyping for CYP2C19 (*2, *3 and *17), CYP3A4*1B and CYP3A5*3 variants was performed in patients (n = 237) who underwent percutaneous coronary intervention. Adenosine diphosphate-induced platelet aggregation was determined after first administration of 600 mg clopidogrel.Results: CYP2C19*2 carriers showed significantly increased residual platelet aggregation (RPA) (OR: 4.6; 95% CI: 2.5––8.7; p < 0.0001) compared with noncarriers. All other polymorphisms had no influence on RPA. For the development of a risk score for better prediction of RPA, CYP2C19*2 genotype and previously identified nongenetic risk factors (age >65 years, Type 2 diabetes mellitus, decreased left ventricular function, renal failure and acute coronary syndrome) were analyzed. Multivariable logistic regression analysis showed a significant correlation of the nongenetic factors (χχ 2 = 5.32; p = 0.021) and CYP2C19*2 (χχ 2 = 21.31; p < 0.0001) with high RPA, and an even higher association for the combination of both (χχ 2 = 25.85; p < 0.0001).Conclusions: Prediction of responsiveness after clopidogrel loading dose may substantially be improved by adding CYP2C19*2 genotype to nongenetic risk factors.